Implementation of Process Standards in Early Childhood Learning at TK Ekklesia Pangkalan Kerinci - Seliana Nainggolan; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Early childhood education (ECE) plays a crucial role in supporting children's holistic development. To ensure the quality of learning, the government has established National Education Standards, including process standards that regulate learning implementation to be interactive, inspiring, and enjoyable (Ministry of Education and Culture, 2014). This study aims to analyze the implementation of learning process standards at TK Ekklesia Pangkalan Kerinci. This research uses a qualitative approach with a case study design. Data collection techniques include observation and interviews with the school principal. The results show that learning has been systematically planned through semester programs and daily lesson plans and implemented using a play-based learning approach. The methods used are varied and child-centered. However, challenges arise from parental expectations regarding early literacy and numeracy skills. Overall, the implementation of process standards has been carried out quite well in accordance with early childhood learning principles.